0099 The Use Of Eye Tracking With Simulated Monitors: A Case For Standardisation?. (1st November 2014) - Greig, Paul; Higham, Helen; Nobre, Anna
Abstract : Background: The clinical environment has been described as an 'ergonomic nightmare', 1 in part because equipment is poorly standardised across institutions. A survey conducted locally found in excess of 40 different display layouts in anaesthetic and critical-care monitors alone. Monitor layouts were not even standardised within individual theatre suites. It is known from psychology research that familiarity (memory-orientated cueing) speeds response time and accuracy in visual search tasks, 2, 3 and it is likely that reading values from an unfamiliar display is more mentally taxing than locating equivalent data on a familiar layout. These extra demands are likely to contribute to errors in clinical practice. Methodology: Using simulations of a representative sample of the displays recorded in our survey, mixed with some fictional layouts, we are using a mobile eye-tracking system to measure the effect of familiarity on speed, accuracy, and mental workload when using clinical displays. Expected results: These data will enable conclusions to be drawn on the effect of using non-standardised clinical monitors. Participants self-rate their familiarity with each display using a visual analogue scale, while their accuracy, time to locate search items, search order, and number/spread of eye-movements are recorded by the eye-tracker. It should also be possible to assess whether professional background or seniority is relevant, and whether participants search for items by colour, expected screen location, or numerical value. Impact: Equipment purchases represent significant capital costs for NHS providers, and clinical devices will generally remain in use for several years. Accordingly only the most appropriate devices should be selected, however it is likely that primarily financial motivators drive many of these decisions. We intend that our data will enable better-informed and safety-focussed business cases to be made for new equipment provision. References: Reader TW, Flin R, Cuthbertson BH. Communication skills and error in the intensive care unit. Curr Opin Crit Care 2007;13(6):732–6 Summerfield JJ, Lepsien J, Gitelman DR, et alMesulam MM, Nobre AC. Orienting attention based on long-term memory experience. Neuron 2006;49(6):905–16 Summerfield JJ, Rao A, Garside N, Nobre AC. Biasing perception by spatial long-term memory. The Journal Of Neuroscience: The Official Journal Of The Society For Neuroscience 2011;31(42):14952–60